JDAQ, the new TEXTOR data acquisition program - Korten, M.; Krom, J.G. (Fusion engineering and design, 2006)
During the last years many components of the TEXTOR data management system were re-engineered. This new system was successfully used to commission and subsequently to operate TEXTOR following the installation of the Dynamic Ergodic Divertor. This paper gives an overview of one of the main re-engineered components: JDAQ, the Java (or Jülich) Data AcQuisition system. JDAQ is based on the design of, and the experiences with the previous TEXTOR data acquisition systems; it was aimed to be an open, distributed and scalable system. It has almost completely been written in the JAVA object-oriented programming language, reflecting many of the code patterns known from modern software engineering. JDAQ is designed as a four-tier layered system, which can be run on a single node or distributed over a TCP/IP network. The TEXTOR operations during the last two years showed the advantage of a highly flexible, platform independent and modular development. The majority of our diagnostic subsystems have been moved to JDAQ and have been reliably operated in the TEXTOR experimental campaigns.